5. Nesterenko, Vasilii Borisovich (former director of the Institute of Nuclear Physics of the Belarusian Academy of Sciences, director of the non-governmental institute of radiation safety)
About his vain attempts to persuade the top officials of the republic to undertake preventive measures and the reaction of the authorities; Chernobyl-related activities of the Institute 1986-1987; evaluation of the current governmental strategies for combating the consequences of Chernobyl; accumulation of strontium as a main danger for health; about the institution of radiation safety.